Construction Ergonomics: Concrete Bit Wear Increases Handle Vibration and Drilling Time. (September 2017) - Rempel, David; Antonucci, Andrea; Barr, Alan; Martin, Bernard
The use of large electric hammer and pneumatic drills exposes construction workers to high levels of hand vibration that may lead to hand arm vibration syndrome and other musculoskeletal disorders. This hammer drill test bench study demonstrated a small but significant increase in z-axis handle vibration (4.8 to 5.1 m/s2; ISO weighted) and drilling time per hole (7.8 to 12.3 s) with worn concrete bits when compared to a new bit. Drill bit manufactures may consider advising contractors that worn bits will increase the exposure of workers to hand vibration and will reduce worker productivity. Construction contractors should adopt a bit replacement program based on bit wear patterns in order to reduce exposure level and drilling time to hazardous hand vibration.